2021
DOI: 10.3390/nano11051189
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatible Magnetic Colloidal Suspension Used as a Tool for Localized Hyperthermia in Human Breast Adenocarcinoma Cells: Physicochemical Analysis and Complex In Vitro Biological Profile

Abstract: Magnetic iron oxide nanoparticles are the most desired nanomaterials for biomedical applications due to their unique physiochemical properties. A facile single-step process for the preparation of a highly stable and biocompatible magnetic colloidal suspension based on citric-acid-coated magnetic iron oxide nanoparticles used as an effective heating source for the hyperthermia treatment of cancer cells is presented. The physicochemical analysis revealed that the magnetic colloidal suspension had a z-average dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
(84 reference statements)
3
5
0
Order By: Relevance
“…The Fe 3 O 4 @C aqueous suspension was highly negatively charged (−47.48 mV) with a narrow size distribution and a single family of nanoparticles. Our results are in agreement with other research studies [61,[88][89][90].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The Fe 3 O 4 @C aqueous suspension was highly negatively charged (−47.48 mV) with a narrow size distribution and a single family of nanoparticles. Our results are in agreement with other research studies [61,[88][89][90].…”
Section: Discussionsupporting
confidence: 94%
“…In order to assess the particle size and distribution, we prepared an aqueous suspension according to the method described in previous research published recently by our group [61]. The hydrodynamic diameter of the Fe 3 O 4 @C nanoparticles was determined at 25 • C, and from Figure 4 it can be observed that the nanoparticles were monomodal in nature.…”
Section: Dls Measurementsmentioning
confidence: 99%
“…The XRF analysis showed that the IONPs obtained by green synthesis could be used in biomedical applications because none of the samples obtained contains traces of metals which can be harmful in healthy living organism. This aspect is in agreement with other research studies, which affirm that nanoparticles based on iron oxides are biocompatible having a great attraction in biomedical treatments due to their non-toxicity [22][23][24][25][26][80][81][82].…”
Section: Xrf Analysissupporting
confidence: 93%
“…G-M55 revealed good performances as a bimodal diagnostic contrast agent and as a therapeutic agent in MFH, with either standard or MPI-based systems. Our results demonstrate the efficacy of MFH in the treatment of breast cancer [ 8 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 57%